PROMOTING PHYSICAL AND SPIRITUAL WELL-BEING AMONG ISLAMIC BOARDING SCHOOL STUDENTS THROUGH OPTIMIZED REPRODUCTIVE HEALTH EDUCATION AND WATER CONSERVATION INITIATIVES - Wiwik Afridah; Prihartini Widiyanti; Achmad Syafiuddin; Gerry Antolin Nesta; Rachmania Devi Wulandari (Community Service Journal of Indonesia, 2026)
Background: The well-being of Islamic boarding school students (santri) is particularly important during puberty, a period characterized by significant hormonal, emotional, and psychological changes. Adequate understanding of reproductive health is therefore essential. This activity aimed to identify reproductive health from multiple perspectives, including psychological and spiritual dimensions, in order to prepare santri to independently maintain their reproductive health. In addition, a demonstration of water-saving faucet installation was conducted to promote water conservation practices. Methods: The participants were 22 santri serving as health cadres (kader husada). Data were collected through focus group discussions (FGDs), guided by key questions regarding the students’ experiences and perceptions of well-being (psychological and spiritual) in relation to reproductive health, as well as their efforts to conserve water within the Islamic boarding school environment. Results and Discussion: Overall, the participants demonstrated readiness and potential to become independent individuals who are physically and mentally healthy, while also showing concern for responsible water use. The well-being of the santri was reflected in their initiative, discipline, and problem-solving abilities. They also played an active role in providing reproductive health education to their peers, supported by adequate facilities and appropriate mentoring. These findings suggest that strengthening reproductive health education alongside environmental awareness programs can contribute to the holistic development and well-being of santri.